The Role of STOPE Framework in the Effectiveness of E-Catalog at the Ministry of Public Works and Public Housing - Rina Wibowo; Erwin Saraswati; Sari Atmini (Eduvest - Journal of Universal Studies, 2025)
The implementation of sectoral e-catalogs is a crucial part of government procurement reform, aiming to enhance transparency, accountability, and efficiency. However, its effectiveness still encounters several challenges in practice. Understanding the influencing factors is essential for optimizing the system.. This study adopts a quantitative approach using a survey method. The respondents are employees of the Ministry of Public Works and Public Housing who are directly involved in the management and use of sectoral e-catalogs. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the STOPE (Strategy, Technology, Organization, People, Environment) framework as the theoretical basis. The findings reveal that strategic, technological, organizational, and people-related factors have a positive and significant effect on the effectiveness of sectoral e-catalog implementation. In contrast, environmental factors did not show a significant impact. The results highlight the importance of strengthening internal capacity and alignment across strategic, technological, organizational, and human resource dimensions to improve e-catalog performance. These insights are valuable for developing more adaptive and responsive electronic procurement policies in the public sector.